Novel plasma biomarkers in arrhythmogenic cardiomyopathy: the role of ST2 and GDF-15 in predicting biventricular involvement. (25th November 2020) - Akdis, D; Chen, L; Saguner, A.M; Zhang, N; Gawinecka, J; Saleh, L; Von Eckardstein, A; Ren, J; Matter, C; Hu, Z; Ruschitzka, F; Chen, X; et al.
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited heart muscle disease characterized by fibrofatty replacement of the myocardium and ventricular arrhythmias. Biventricular (BiV) involvement in ARVC may lead to heart failure. Purpose: This study aimed to investigate the role of novel plasma biomarkers soluble (s)ST2, Galectin-3 (Gal-3) and GDF-15 in predicting BiV involvement and adverse outcomes in ARVC patients. Methods: ARVC patients from two independent cohorts were studied. 108 patients were included from the discovery cohort and 47 patients were included from a second validation cohort. All patients had a definite ARVC diagnosis at time of blood withdrawal. sST2, Gal-3 and GDF-15 were independently correlated with NT-proBNP, left ventricular (LV) ejection fraction, late gadolinium enhancement by cardiac magnetic resonance (CMR) imaging and clinical outcome. Results: ARVC patients with LV involvement had higher levels of sST2 and GDF-15 as compared to controls and patients with isolated right ventricular involvement. sST2 and GDF-15 significantly correlated to late gadolinium enhancement on CMR and also correlated to adverse heart failure outcomes. Gal-3 was elevated in ARVC patients with and without LV involvement as compared to controls. The combined use of the three biomarkers (NT-proBNP, sST2 and GDF-15) showed the best performance in predicting LV involvement in both the discovery and the validation cohort. Plasma drawn from coronary arteries and coronary sinus showed a transmyocardial elevation of sST2. Conclusion: Our study shows that sST2 and GDF-15 may predict BiV involvement and the combined use of NT-proBNP, sST2 and GDF-15 shows the best prediction of LV involvement in ARVC. Transmyocardial elevation of sST2 suggests that this biomarker is produced by myocardial tissue in ARVC. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Fuwai ARVC Program was supported by CAMS Innovation Fund for Medical Sciences and the National Natural Science Foundation of China, Zurich ARVC Program was supported by grants from the Schwyzer Foundation and Baugarten Foundation